Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1967
DOI: 10.1017/s0022112067001934
|View full text |Cite
|
Sign up to set email alerts
|

Potential flow about two-dimensional hydrofoils

Abstract: This paper describes a very general method for determining the steady two-dimensional potential flow about one or more bodies of arbitrary shape operating at arbitrary Froude number near a free surface. The boundary condition of zero velocity (solid wall) or prescribed velocity (suction or blowing) normal to the body surface is satisfied exactly, and the boundary condition of constant pressure on the free surface is satisfied using the classic small-wave approximation. Calculations made by the present method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…23 with the surface of the NACA-4412 hydrofoil at = 5 ∘ and = 1.03 for two submergence depths. In addition, the present results are verified and validated by comparing them with the numerical results reported by Giesing and Smith [13] and the experimental data reported by Ausman [3]. Furthermore, Giesing and Smith [13] assume a 2D linearized potential flow and apply a BEM.…”
Section: Hydrodynamic Behavior Of a Steadily Translating Hydrofoilsupporting
confidence: 82%
See 4 more Smart Citations
“…23 with the surface of the NACA-4412 hydrofoil at = 5 ∘ and = 1.03 for two submergence depths. In addition, the present results are verified and validated by comparing them with the numerical results reported by Giesing and Smith [13] and the experimental data reported by Ausman [3]. Furthermore, Giesing and Smith [13] assume a 2D linearized potential flow and apply a BEM.…”
Section: Hydrodynamic Behavior Of a Steadily Translating Hydrofoilsupporting
confidence: 82%
“…In addition, the present results are verified and validated by comparing them with the numerical results reported by Giesing and Smith [13] and the experimental data reported by Ausman [3]. Furthermore, Giesing and Smith [13] assume a 2D linearized potential flow and apply a BEM. This study is more consistent with the numerical results reported by Giesing and Smith [13] than with the experimental results.…”
Section: Hydrodynamic Behavior Of a Steadily Translating Hydrofoilsupporting
confidence: 82%
See 3 more Smart Citations